Pendampingan Penyusunan Proposal Bisnis UKM bagi Masyarakat Desa Cileunyi Wetan di Kabupaten Bandung - Iwan Mulyana (LPPM Universitas Koperasi Indonesia, 2023)
Assistance in the preparation of small and medium business proposals is an activity carried outroutinely by Cileunyi Wetan Village to provide assistance by assisting the UKM community who areinterested in preparing business proposals. The method is carried out by directly assisting inpreparing business proposals that will be submitted to creditors, this activity is carried out at theCileunyi Wetan Village Building by Lecturers from the Indonesian Cooperative University. Throughthe provision of material, question and answer, and assistance in preparing proposals directly toparticipants. The material provided to the public is credit and preparation of business proposals.While the discussion was carried out after giving the material. The last session is preparing businessproposals with direct assistance until the participants understand. This mentoring activity is used asa basis for assisting participants in submitting their business funding so that it is ready to besubmitted to the relevant institution.